Curriculum content and assessment of pre‐clinical dental skills: A survey of undergraduate dental education in Europe. (21st June 2017) - Field, J.; Stone, S.; Orsini, C.; Hussain, A.; Vital, S.; Crothers, A.; Walmsley, D.
Abstract: Introduction: Since 1981, the qualifications for various healthcare professionals across the European Union have enjoyed mutual recognition in accordance with the EU Directive 81/1057/EEC. Whilst the directive includes dental practitioners, it is recognised that significant variation exists in curriculum structure, content and scope of practice across institutions. This article aimed to explore pan‐European practice in relation to curriculum content, teaching and learning strategies and assessment of pre‐clinical dental skills. Method: A request to complete an online questionnaire, in English, was sent electronically to skills leads at all Association of Dental Education in Europe member schools. The questionnaire collected information in relation to institution and country, regulatory requirements to demonstrate safety, details of specific pre‐clinical skills courses, learning materials and teaching staff. Results: Forty‐eight institutions, from 25 European countries responded. Seven countries (n=7, 28%) reported no requirement to demonstrate student operative safety prior to patient treatment. Several core and operative clinical skills are common to the majority of institutions. The most commonly taught core skills related directly to the clinical environment such as cross‐infection control and hand washing. The least common were skills that indirectly related to patient care, such as communication skills and working as a team. Conclusion: There are clear differences within European pre‐clinical dental education, and greater efforts are needed to demonstrate that all European students are fit to practice before they start treating patients. Learning outcomes, teaching activities and assessment activities of pre‐clinical skills should be shared collaboratively to further standardise curricula.